Hubungan Pemberian ASI Dan Susu Dot Dengan Tambahan Makanan Pendamping ASI Pada Perkembangan Bicara Bayi Usia 9-12 Bulan - Rahayu, Titik Dwi, Agus Widodo, S.Fis., M.Fis (2016)
Purpose: To know the relation of breastfeed and breastfeed pacifier with additional complementary feeding to verbal development of baby aged 9 - 12 months. Background: Reflek rooting is early process of breastfeeding where the baby looking for the nipple followed refleks sucking and swallowing. The refleks appears when baby giving breastfeed or breastfeed pacifier. Breastfeeding will not be enough to supply nutritional needs of baby, so at the age of 6 months through a phase of complementary feeding where the baby not only suck and swallow, but chewing food its involves muscle verbal shaper which plays an important role in development of verbal. Verbal process be produced by vibration of the vocal cords. While sound created by lip, tongue, and palatum (top of the oral cavity) vibration. Subject: 9-12 month baby who visited in Baby Spa Sarila Family Care from 26 October until 26 November, obtained subject 60 babies were divided into 3 groups, with 20 respondents breastfeed - complementary feeding, 20 respondents breastfeed - complementary feeding and 20 respondents breastfeed+ breastfeed pacifier - complementary feeding. Methods: Type of this research is Observasional with design research Cross Sectional. Sampling technique this research is Purposive Sampling. Measuring instrument of verbal ability using Early Language Milestone Scale-2. Statistic analysis using Chi Squere with degree of confident 95% (ρ = 0,05). Result: Based result of statistic test obtained there is relation between 3 variable. With ρ = 0,023 (ρ ≤ 0,05) which mean H0 ignored or Ha accepted. It can be concluded that there is relation between breastfeed, breastfeed pacifier and complementary feeding to verbal development of baby aged 9 - 12 months in Baby Spa Sarila Family Care Sragen. Conclusion: There is relation between breastfeed, breastfeed pacifier and complementary feeding to verbal development of baby aged 9 - 12 months in Baby Spa Sarila Family Care Sragen. Keywords : verbal development of baby, breastfeed, breastfeed pacifier and complementary feeding.